Effect of Dorsal Preservation Techniques on Septum Strength: An Experimental Animal Study - Erol, Ozan; Berber, Veysel; Soto-Galindo, Germán Armando; Apaydin, Fazil (Facial Plastic Surgery, 2024)
This experimental animal model study investigates the impact of different methods employed in preservation rhinoplasty (PR) on the strength of the nasal roof, focusing on three techniques: high strip, low strip, and intermediate strip. Using 15 lamb heads as surgical models, the study addresses key questions related to the strengths of each PR techniques, the influence of septal cartilage harvesting on septum strength, and the effectiveness of spreader grafts for stability. The research involves detailed dissection steps and measurements at various nasal points, evaluating the resistance at each stage. Results indicate that the low strip technique demonstrates the most significant reduction in strength. Furthermore, the combination of PR techniques with structural grafts, specifically spreader grafts, is assessed, revealing the classical rectangular spreader graft to be more effective in stabilizing the dorsum. Despite the limitation of using the lamb heads as models, this study offers valuable insights into the effects of PR on nasal septum strength and provides a foundation for further research on the biomechanics of preservation techniques.
Keywords: biomechanics; preservation rhinoplasty; low strip; high strip; intermediate strip; strip